SINTESIS 2,5âbis(4ââHIDROKSIâ5ââKLOROâ3ââMETOKSIBENZILIDIN) SIKLOPENTANON DAN UJI AKTIVITASNYA SEBAGAI ANTIOKSIDAN - , warsi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A study was performed to obtain a curcumin analogue compound which ha âCl substituent in the aromatic ring i.e. 2,5âbis(5ââchloroâ4ââhydroxyâ3ââ methoxybenzylidene)cyclopentanone. The synthesis of this compound was carried out by condensation of cyclopentanone with chlorinated vanilin (5âchloroâ4â hydroxyâ3âmethoxybenzaldehyde). This compound has been identified. Its activity as an antioxidant using DPPH (1,1âdiphenylâ2âpicrylhydrazyl) radical scavenging and the ô-caroteneâlinoleic acid methods have been investigated. Th Chlorination reaction of vanillin performed using Cl2 gas, which produced by reaction of kaporit with concentrated hydrochloric acid. e reaction occured at 35ÂºC for 30 minutes, with the AlCl3 as a catalyst and THF as the solvent. It produced a yellow compound of 5âchloroâ4âhydroxyâ3âmethoxybenzaldehyde. The average yield was 40.54 % and the melting point was 163.3â164.8ÂºC. Then, 5âchloroâ4âhydroxyâ3âmethoxybenzaldehyde was condensed with cyclopen- tanone to form a greenâyellow compound of 2,5âbis(5ââchloroâ4â Hydroxyl â 3ââ methoxybenzylidene)cyclopentanone. This condensation reaction occured at room temperature for 4 hours, under acidic conditions and THF as the solvent. The reaction mixture was set aside for 6 days. The average yield is 49,77 % and the melting point of 268.0â270.0ÂºC. The purity of the synthesized compounds were determined by Thin Layer Chromatography and High Performance Liquid Chromatography. The structure elucidation of this synthesized compounds have been performed using spectroscopy techniques, including infrared, nuclear magnetic resonance proton, nuclear magnetic resonance carbon and mass spectrometry. â The antioxidant activity of synthesized product was determined by DPPH radical scavenging method and the absorbance was measured by the UV Vis spectrophotometer at ômax of 517 nm. The synthesized compound showed the activity of DPPH radical scavenging metode (IC50 184.23 ôM). Its potency as an antioxidant was lower than PGVâ0 (IC50 26.76 ôM) and curcumin (IC50 13.69 ôM). The potency of antioxidant activity of synthesized product was also determined based on inhibition of the ô-carotene bleaching by the linoleic acid radical and the absorbance was measured by the UVâVis spectrophotometer at ômax of 450 nm. The result of this method obtained EC50 value of 23.04 ôM. The antioxidant potency of the sample was more potent than those curcumin (EC50 25.86 ôM) and PGVâ0 (EC50 32.15 ôM).